The age of calamities : stories - Ahmad, Senaa (Henry Holt and Company, 2026)
"In this bold and enchanting collection Senaa Ahmad takes license with history and its players, sending the reader on a thrilling ride. In "Let's Play Dead," Henry VIII wants Anne Boleyn gone, but there's a tiny problem, she keeps coming back to life no matter what he does. "Choose Your Own Apocalypse" hurls readers back to 1945, where they assume the role of a technician for the Manhattan Project, surrounded by labyrinthine paths and harrowing outcomes. And "Inside the House of the Historian" invites us to a dinner party turned murder mystery full of figures like Nefertiti, Queen Victoria, John Adams, and Marilyn Monroe. These stories and others entice readers to confront the past, the present, and themselves all at once. Zany and haunting, inviting and brilliant, each poignant tale delves into surreal nature of today through the lens of yesterday, charting the tragicomic yet hopeful act of living..""-- Provided by publisher.